Living and Growing Within a Museum: re-creating video art for preservation - Ana Ribeiro (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
This paper explores the consequences of obsolete phenomena in video art installations and their potential in re-creating works of art within the conservation process. Through Klaus vom Bruch’s Das Ende des Jahrhunderts and Jonathan Horowitz’s Mon.-Sun, it is aimed to understand the creative process that starts at the artists’ studios and follows the artwork through its life within a museum collection.